الفنون البيانية في ديواني الرياض والسباعيات للشاعر النيجيري عيس ألبي أبو بكر دراسة بلاغية وتحليلية - ادم أديشينا أحمد
This study aims to present the figurative language in the collected works of "Deewan Al-Riyadh" and "Deewan As-Sibaiy'aaht" by the Nigerian poet Issa Alabi Abu Bakr and its analytical rhetoric research. The problem of the study lies in the scarcity of past research on the collected works of this Nigerian poet. Moreover, these studies do not satisfy the rhetorical aspect. Instead, they focus mostly on the areas of grammar, morphology, and criticisms. Thus, this current study focuses on the rhetorical aspect in revealing the forms of figurative language contained in the "Deewan Al-Riyadh" and "Deewan As-Sabahyi'aaht." The researcher highlights the similes (Tashbeeh), metaphors (Isti'ariah), metonymies (Kinaiyyah) and allegories (majaziah) inherent in both works. In this study, the researcher employs the descriptive analysis method to examine the total of (315) poetic verses in both works and analyses them rhetorically. The study has reached several results, one of the most important being: The Nigerian poet Issa Alabi is one of the greatest Nigerian poets, and his poems are full of figurative language. The researcher’s focus is to identify evidence of the uses of figurative language in both works. Deewan Al-Riyadh carries a total of (164) figurative language. There are (71) similes and (40) metaphors of various types and a total of (34) metonymies, as well as (39) allegories. While in "Deewan As-Sibahiy'aaht," there are approximately (151) uses of figurative language. There are (74) similes and (20) metaphors. There are also (45) metonymies and (12) allegories. Therefore, the study concludes that the use of simile is more frequent in both works.